Registration of 'Hardy 2519' wheat. Issue 2 (16th April 2022) - Liu, Limei; Griffey, Carl Allen; Brooks, Wynse S.; Seago, John E.; Fitzgerald, Joshua; Thomason, Wade; Hokanson, Elizabeth G.; Behl, Harry D.; Oakes, Joseph; Pitman, Robert M.; Dunaway, David W.; Vaughn, Mark E.; et al.
Abstract: 'Hardy 2519' (Reg. no. CV‐1189, PI 692613), a hard red winter (HRW) wheat ( Triticum aestivum L.) cultivar, was derived from the cross VA06HRW‐108 × 'Vision 30' (PI 661153) using a modified bulk breeding method. Hardy 2519 was tested as VA14HRW‐25 in replicated yield trials in Virginia (2015–2018) and in the USDA‐ARS Uniform Bread Wheat Trials (2016–2018) and released by the Virginia Agricultural Experiment Station in 2019. Hardy 2519 is a widely adapted, high‐yielding HRW wheat with 2*, 5+10 gluten subunits. Hardy 2519 is awned, semidwarf ( Rht 2 gene) with medium spike emergence, resistant to leaf rust, and moderately resistant to powdery mildew in the mid‐Atlantic region. In the Virginia Bread Wheat Elite Trials from 2018 to 2020, Hardy 2519 produced a mean yield of 5, 393 kg ha –1, which was similar to that of the HRW wheat cultivar 'Vision 45' (PI 667642) at 5, 267 kg ha –1 . Hardy 2519 has acceptable milling and baking quality on the basis of comparisons with the HRW wheat check cultivar 'Jagger'. Core Ideas: Hardy 2519 is a hard red winter wheat. Hardy 2519 has high yield potential. Hardy 2519 resists leaf rust.